2006
DOI: 10.1080/00220380500356225
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and fragmentation: Transactions costs and the value of aid

Abstract: The problem of the proliferation of the number of aid donors and aid channels continues to worsen. It is widely and plausibly believed that this significantly reduces the value of aid by increasing direct and indirect transactions costs. We contribute to the existing literature by: (a) categorising the apparent adverse effects of proliferation; (b) producing a reliable and fair indicator of the relative degree to which the main bilateral donors proliferate or concentrate their aid; (c) giving some explanation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
221
0
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 240 publications
(230 citation statements)
references
References 11 publications
(12 reference statements)
1
221
0
4
Order By: Relevance
“…As it clearly indicates, the number of ODA projects has been steadily increasing. 1973 1975 1977 1979 1981 1983 1985 1987 1989 1991 1993 1995 1997 1999 Acharya et al (2006) suggested that aid often underperforms because it flows through too many institutional channels. There are huge transaction costs associated with aid proliferation (an increase in the number of donors to a specific recipient country) and aid fragmentation (an increase in the number of projects and a decline in the amount per project) for both recipients and donors.…”
Section: Aid Proliferation Fragmentation and Transaction Costsmentioning
confidence: 99%
See 4 more Smart Citations
“…As it clearly indicates, the number of ODA projects has been steadily increasing. 1973 1975 1977 1979 1981 1983 1985 1987 1989 1991 1993 1995 1997 1999 Acharya et al (2006) suggested that aid often underperforms because it flows through too many institutional channels. There are huge transaction costs associated with aid proliferation (an increase in the number of donors to a specific recipient country) and aid fragmentation (an increase in the number of projects and a decline in the amount per project) for both recipients and donors.…”
Section: Aid Proliferation Fragmentation and Transaction Costsmentioning
confidence: 99%
“…Acharya et al (2006) produced an index of donor proliferation using the inverse (multiplied by 100) of the Theil index of each donor's ODA delivered in 1999-2001 to its potential recipients.…”
Section: Aid Proliferation Fragmentation and Transaction Costsmentioning
confidence: 99%
See 3 more Smart Citations